Transcriptional activity of the human pseudogene psi alpha globin compared with alpha globin, its functional gene counterpart. - Whitelaw, E; Proudfoot, N (1983)
Transcriptional analysis of the human pseudogene psi alpha globin has revealed the following features: (1) The promoter with a 23 bp deletion between the CCAAT and ATA boxes is functional both in vitro and in vivo, 3 fold and 10 fold less efficient, respectively, than alpha. (2) Both the psi alpha and alpha globin gene promoters are active in the absence of transcriptional enhancers, either a gene-encoded or viral enhancer. (3) The mutated poly(A) addition signal in psi alpha (AATGAA) appears to be completely nonfunctional. This result provides an explanation for the absence of psi alpha transcripts in human erythroid cells.